Peranan Komunikasi Sosial Menurut Inter Mirifica dalam Kehidupan Orang Muda Katolik di Kub Sta Maria dari Gunung Karmel Paroki Sta Maria Assumpta - Susana Li; Gerardus B. Duka; Florens Maxi Un Bria (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the role of social communication based on the Inter Mirifica document in the lives of Catholic Youth (OMK) at the Sta. Maria of Mount Carmel Parish, Sta. Maria Assumpta Kupang. The rapid development of digital communication media has significantly influenced the faith, social relationships, and pastoral participation of Catholic youth, creating both opportunities and challenges for the Church. This study employed a descriptive qualitative method. Data were collected through interviews, observation, and documentation involving Catholic Youth members, the Head of OMK, the Head of KUB, and the Parish Priest. The data were analyzed through data collection, reduction, presentation, and conclusion drawing. The findings reveal that social media platforms, including WhatsApp, Instagram, Facebook, and YouTube, play an important role in facilitating communication, disseminating information about church activities, strengthening faith formation, and fostering relationships among community members. However, excessive use of social media may expose young people to content inconsistent with Christian values, reduce direct interpersonal communication, and weaken spiritual life. Therefore, the Church should strengthen pastoral guidance, digital literacy, and responsible social communication to help Catholic youth use digital media wisely, critically, and in accordance with Christian values.